Another look at contagion across United States and European financial markets: Evidence from the credit default swaps markets. (18th January 2021) - Tsionas, Mike G.; Apergis, Nicholas
Abstract: The paper looks at the results of Apergis, Christou and Kynigakis (2019) and proposes a novel model that allows time variation in volatility, skewness and kurtosis, based on multivariate stable distributions. The analysis also looks at bank sector CDS, insurance sector CDS, sovereign bonds, equity and volatility indices. The findings corroborate their results and indicate significant evidence of contagion, especially through the channels of co‐skewness and co‐kurtosis. In addition, it establishes a higher order channel of causality between co‐skewness and co‐kurtosis.